A facile approach to [1, 2, 4]triazolo[3, 4‐i]purine via PIDA oxidation ring‐closing reaction. (8th August 2021) - Sun, Xiangbin; Yu, Mingwu; Mu, Xianfeng; Zhou, Zheng; Wang, Linqing; Liu, Jianhui; Liu, Xiguang
Abstract: A facile conversion of 6‐(2‐arylidenehydrazineyl) purines to [1, 2, 4] triazolo [3, 4‐i] purines is presented using PhI(OAc)2 as oxidant in only 10 min under room temperature. This approach is metal‐free, wide functional group tolerant, and provides an efficient and convenient method to synthesize purine‐fused tricyclics. Abstract : A facile conversion of 6‐(2‐arylidenehydrazineyl) purines to [1, 2, 4] triazolo [3, 4‐i] purines is presented by using PhI(OAc)2 as oxidant in 10 min under room temperature, which is metal‐free, wide functional group tolerance, and provides a convenient method to synthesize purine‐fused tricyclics.